Basic problems of the European Community - Dagtoglou, P. D. (Oxford [Eng.] : B. Blackwell, 1975)
This volume includes nine contributions. All nine essays are concerned with basic problems of the community, in the sense of questions relating to the degree of present and future political stability and viability of the community and the process of European integration.
Includes bibliographical references and index.
osc 19/10/2018
Loans